KNOWLEDGE AND ATTITUDE OF TELEMEDICINE AMONG CAREGIVERS OF PEDIATRIC EPILEPSY PATIENTS -A CROSS-SECTIONAL STUDY - Dr. Prajna Bhushan; Dr. K.B. Mahendrappa (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
INTRODUCTION: Telemedicine combines advanced telecommunications and electronic information technologies to provide healthcare services even at remote areas. It is an essential and beneficial technology that can ease preventive treatment and improve long-term health. In addition, it can make healthcare more efficient, organized, and available. We sought to understand the knowledge and attitude of telemedicine among the parent/ guardian of epilepsy patients. OBJECTIVE”: To assess the knowledge and attitude regarding telemedicine among pediatric caregivers of epilepsy patients. MATERIALS AND METHODS: A cross-sectional study was conducted in the Department of Pediatrics, Adichunchanagiri Hospital and Research centre between October 2024 and December 2024, utilizing self-administered questionnaires for data collection. In this study, the non-probability purposive sampling method was adopted. All caregivers (aged 18 years or older) of paediatric epilepsy patients visiting OPD or admitted patients who have been involved in the patient’s care for at least 6 months were included in the study and were provided with a questionnaire which comprised three main sections: demographics, knowledge and attitude Regarding caregivers’ knowledge. Statistical Package for Social Sciences (SPSS) version 22.0 was used for data analysis. RESULTS: Among the 88 participants in the study, the majority (42%) were aged between 26 and 30 years, and 73.9% were female. In the study the level of awareness about telemedicine was low as only 28.4% had heard of telemedicine. Most participants were able to correctly identify its purposes and benefits. All aspects of the caregivers’ attitudes demonstrated posi¬tive agreement with the Likert scale of attitudes. CONCLUSION: Our research uncovered a significant knowledge gap regarding telemedicine services, including their availability, purposes, and benefits. However, caregivers demonstrated positive attitudes toward telemedicine, with social media emerging as the most effective platform for awareness and education.